Motherhood and modernity - Bravo de Rueda, María del Carmen (2007)
The purpose of this abstract is to analyze the social and labor situation changes in the life of the middle class woman worker and resident of a city, in the last decades, and their influence in the way she experienced the motherhood at present. Discomfort and problems were examined and their alternative solutions presented. For this research, printed as well as on line articles and statistical data have been examined.